2023
DOI: 10.3390/jmmp7020064
|View full text |Cite
|
Sign up to set email alerts
|

Recoater-Induced Distortions and Build Failures in Selective Laser Melting of Thin-Walled Ti6Al4V Parts

Abstract: Additively manufactured thin-walled structures through selective laser melting (SLM) are of great interest in achieving carbon-neutral industrial manufacturing. However, residual stresses and warpages as well as recoater crashes often occur in SLM, leading to the build failure of parts, especially for large-scale and lightweight geometries. The challenge in this work consists of investigating how the recoater affects the warpage and (sometimes) causes the failure of different thin-walled Ti6Al4V parts (wall th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…These studies delve into SLM's capabilities in producing intricate and lightweight components for various industries. Their findings contribute to advancing AM techniques and applications [48][49][50][51]. Studies have shown that the quality and reliability of thin-walled products produced using SLM are significantly influenced by various process parameters, including powder layer thickness, hatching distance, and laser power [50,52].…”
Section: Selective Laser Melting For Thin-walled Partsmentioning
confidence: 94%
“…These studies delve into SLM's capabilities in producing intricate and lightweight components for various industries. Their findings contribute to advancing AM techniques and applications [48][49][50][51]. Studies have shown that the quality and reliability of thin-walled products produced using SLM are significantly influenced by various process parameters, including powder layer thickness, hatching distance, and laser power [50,52].…”
Section: Selective Laser Melting For Thin-walled Partsmentioning
confidence: 94%
“…Adapted from ref. [29]. The heat exchange was defined also for the specimen using the same parameters previously discussed for the heat exchange between the plate and the environment.…”
Section: Fem Model For L-pbfmentioning
confidence: 99%
“…Cheng et al [41] compared the experimental results with the Simufact simulation tool, where they used a multiscale approach method to analyse the part distortion. Some authors investigated the prediction of distortion, using a method incorporating a mathematical heat source model for thermo-mechanical finite element analysis -FEA [42]. This was a method where the powder is considered as the input material.…”
Section: Introductionmentioning
confidence: 99%